Desarrollo de un juego educativo en el área de Matemática para estudiantes con discalculia ideognóstica - Guevara Samaniego, Manuel Oswaldo (2024)
The purpose of this research was to design an educational game for children with ideognostic dyscalculia. Ideognostic dyscalculia refers to the problem of understanding concepts, establishing relationships and solving mathematical operations “summing, subtraction, multiplication and division". In order to carry out this work we decided on a type of applied research since it aims to generate knowledge with direct applications to the problem, it is technological design because it seeks technological innovation for the resolution of socio-educational problems and we used the methodology of extreme programming (XP). Finally, it was possible to implement an educational game that will support the learning process of 6th and 7th year EGB students with ideognostic dyscalculia, which was developed in Java version [JavaSE-17], using the programming IDE Eclipse in its version 2023-09 (4.29.0).